A LINGUA MATERNA ALAVANCANDO MECANISMOS DE SOCIALIDADE EM CURSO DE INGLÊS PARA HOTELARIA - Terra, Márcia Regina (Intercâmbio, 2010)
From a vygotskian theory perspective, the learning of English for Specific Purposesis examined by the teacher and nine hotel employee.The focus is on the use of the mother tongue in this process. It is found that the MT plays a central role in the building of students’ discursive performance.